Perlindungan Hukum Terhadap Investor dalam Kegiatan Foreign Direct Investment (FDI) Berbentuk Joint Venture: Perbandingan antara Negara Indonesia dan Australia - Takke, Shareen Virgita Septalia (Media Hukum Indonesia (MHI), 2025)
The purpose of the existence of this study is to analyze towards how the legal protection of foreign investors undertaking Foreign Direct Investment in the form of Joint Venture in Indonesia as well as compare its regulation with the legal framework in Australia. This study uses a normative (doctrinal) type of legal research, which focuses on the analysis of law in books to study the regulations in force. The approach used was a statute approach to research the PM Act, PT Act, FATA, and other regulations, as well as a comparative approach to compare the legal system of Joint Venture investor protection between Indonesia and Australia. Data collection was conducted through library study, including primary (legislative regulations, international agreements) and secondary (journals, books) legal materials. All legal materials were analyzed qualitatively and descriptively, aiming to exhibit the results of the comparison in a structured, systematic, and thorough manner. The results of the study show that Based on the Comparison of the Regulation of Legal Protection of Investors in Foreign Direct Investment (FDI) in the Form of Joint Venture between Indonesia and Australia, it can be noted that there are fundamental differences in the philosophy of investment protection between Indonesia and Australia. Indonesia adheres to a state-controlled regime approach in which the state has predominant authority in supervising and restricting foreign investment in order to protect its economic sovereignty. In contrast, Australia adheres to a risk-based liberal-regulatory approach through the Foreign Acquisitions and Takeovers Act 1975 (FATA) which only intervenes if an investment is assessed as significant action or threatening the national interest (negative test).